Examination of The Attitudes of Cycling Athletes' Towards Ecorecreation - Albayrak, Veysel; Gacar, Atalay; Nacar, Eyyup; Tutar, Omer Faruk (Lahore Medical Research Center Llp, 2021)
Background: It is known that people's relations with nature can be greatly influential in all periods of their lives and especially in their future, which has increased their interest in concepts such as environment, nature, natural life, ecology, ecosystem as a result of the increase in natural awareness in humans. Aim: Based on these ideas, our research aims to measure the attitudes of cycling athletes in Elazig province towards ecorecreation.. Methods: A total of 178 athletes from 242 cycling athletes, including cycling sports clubs, associations, and individual athletes in Elazig province, participated voluntarily. It consists of 31 substances and 6 sub-dimensions developed by Ayyildiz and the 'Personal Information Form' prepared by the researchers as a data collection tool. Attitude Scale Towards Ecorecreation(ASTE), which was created in a 5-point Likert type format, was used. Spss 22.00 package program was used for the analysis of the data and the level of significance was determined as p<0.05. In the study, t-test analysis was applied to determine the significance of the differences between two groups and ANOVA was applied to determine the significance between more than two groups. Pearson correlation analysis was used to determine the direction and severity of the relationship between variables. Results: As a result of the research, there was a semantic difference in the individual and environmental sensitivities of licensed cycling athletes. A significant difference was observed in the Attitudes and Behavior towards Ecorecreation sub-dimensions of the athletes who are interested in another nature sport. Conclusion: The increase in positive behaviors towards nature has clearly become clear that it is directly related to being in nature. Accordingly, researchers believe and draw attention to the fact that in order to increase the positive effect on nature, it is necessary to be intertwined with nature and to adopt it.
Keywords: Cycling; Outdoor Sport; Recreation; Ecorecreation